Antibiotic susceptibility and biofilm-forming ability of Veillonella strains. (December 2022) - Li, Junli; Wang, Hejing; Li, Na; Zhang, Yikui; Lü, Xin; Liu, Bianfang
Abstract: Introduction: Veillonella, known as early colonizers in oral biofilms, take part in some infections in human. Biofilm refers to complex, sessile communities of microbes, which function as strong barriers for bacteria to survive. Biofilm matrixes surrounding bacteria enable them to withstand harsh conditions, protect against immune cells, etc., and also make them resistant to antimicrobial treatments. Thus, the knowledge of antibiotic susceptibility and biofilm formation of Veillonella will shed light on their resistance mechanism. Materials and method: Their morphology was observed by scanning electron microscopy (SEM). According to the performance standards for antibiotic susceptibility testing of the Clinical & Laboratory Standards Institute, the Agar dilution method was used to study the susceptibility of Veillonella strains to eight antibiotics (ampicillin, piperacillin-tazobactam, cefoxitin, tetracycline, moxifloxacin, clindamycin, metronidazole, and vancomycin). In addition, we applied the crystal violet staining method to reveal the processes of biofilm formation of these Veillonella strains. Results: V. rogosae, V. nakazawae, and V. parvula were isolated from oral cavities of healthy adults and V. ratti was isolated from dairy goat droppings. Observations by scanning electron microscopy showed that Veillonella were spherical and arranged in single or short chains. The diameter of a single cell was about 0.3–0.5 μm. The Minimum Inhibitory Concentrations (MICs) of the antibiotics were determined and the results showed that these four strains were all sensitive to cefoxitin, tetracycline, moxifloxacin, clindamycin and metronidazole. Among the four strains, V. ratti was resistant to piperacillin-tazobactam, and V. rogosae and V. nakazawae were resistant to ampicillin. The vancomycin susceptibility of the four Veillonella strains varied greatly. The MICs of vancomycin against V. rogosae and V. ratti were greater than 256 μg/mL but the MICs of vancomycin against V. nakazawae and V. parvula were less than 2 μg/mL. V. parvula had significantly higher biofilm-forming ability than the other three strains (p < 0.05) and V. nakazawae had the weakest biofilm-forming ability. Conclusion: In this study, V. rogosae, V. nakazawae, V. parvula and V. ratti were isolated and identified. The four strains of Veillonella showed differences in MIC values for different antibiotics and biofilm-forming ability. Highlights: V. rogosae, V. nakazawae, V. parvula and V. ratti were isolated and identified. The antibiotics sensitivity of Veillonella strains were studied. V. nakazawae and V. parvula couldn't grow even at low concentrations of vancomycin. Biofilm formation was observed in the isolates. V. parvula had a strong biofilm-forming ability.